2018
DOI: 10.2147/dddt.s166989
|View full text |Cite
|
Sign up to set email alerts
|

Development of a tin oxide carrier with mesoporous structure for improving the dissolution rate and oral relative bioavailability of fenofibrate

Abstract: BackgroundBiopharmaceutics classification system class II drugs have low solubility, which limits their extent and speed of absorption after oral administration. Over the years, mesoporous materials have been widely used to increase the dissolution rate and oral relative bioavailability of poorly water-soluble drugs.ObjectivesIn order to improve the dissolution rate and increase oral relative bioavailability of the poorly water-soluble drugs, a tin oxide carrier (MSn) with a mesoporous structure was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…SEM images of the catalyst samples in Figure show a long-rod morphology in a bundle arrangement with a particle size of less than 1 μm. The same morphology is observed for typical SBA-15. , The synthesized materials display typical fibrous type morphologies, indicating that the morphology did not change during the surface modification.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…SEM images of the catalyst samples in Figure show a long-rod morphology in a bundle arrangement with a particle size of less than 1 μm. The same morphology is observed for typical SBA-15. , The synthesized materials display typical fibrous type morphologies, indicating that the morphology did not change during the surface modification.…”
Section: Resultssupporting
confidence: 74%
“…The same morphology is observed for typical SBA-15. 53,54 The synthesized materials display typical fibrous type morphologies, indicating that the morphology did not change during the surface modification.…”
Section: Resultsmentioning
confidence: 94%
“…Compared with other materials, mesoporous tin dioxide, as a metal oxide nanocarrier, has promising applications as a potential pharmaceutical excipient. Andi Bai et al ( Bai et al, 2018 ) used tin dioxide with a mesoporous structure to improve the oral relative bioavailability of fenofibrate, and the results showed that tin dioxide has great potential in improving the aqueous solubility and enhancing the bioavailability of insoluble drugs. In this study, we prepared hollow tin dioxide (HSn) nanocarriers by a hydrothermal synthesis method.…”
Section: Introductionmentioning
confidence: 99%
“…Poorly soluble drugs cause many issues which include dose escalation, low bioavailability, and poor in-vitro and in-vivo drug performance [2]. To curtail this issue, scientists have adopted various approaches, for example micronization, complexation, lipid-based formulations, co-solvents, salt formation, solid dispersions, nano-formulations and many more [3,4]. Among the above-mentioned techniques, nanocarriers, which include drug nanocrystals [5][6][7], nanoemulsions [8][9][10], polymeric micelles [11,12], nanoparticles [13,14], nanotubes [13], and silica-based nanocarriers [15] are widely investigated by scientists.…”
Section: Introductionmentioning
confidence: 99%